Vocational teacher education and training in an international context – trends and recommendations - Spöttl, Georg [Verfasser] (My University, 2022)
„The training of teachers for vocational education is a constant point of discussion in numerous countries. In actual training practice, the “on-the-job” model is dominating, i. e. experience as a teacher is gathered directly in the classroom after a teacher basic training course that often lasts only a few weeks. Stakeholders such as United Nations Educational, Scientific and Cultural Organization (UNESCO), International Centre for Technical and Vocational Education and Training (UNESO- UNEVOC), International Labour Organization (ILO), Asian Development Bank (ADB) and other organizations offer guidelines for improving the quality of teacher training, but most of them deal with the framework of teacher training rather than with the core requirements. Based on a professionally oriented reference profile for teachers, the article shows which requirements are crucial for these professional groups. Subsequently, the positions of selected stakeholders and individual countries on teacher training for Technical Education and Vocational Training are analyzed. Based on these findings and the Hangzhou Standards of UNESCO-UNEVOC, standards for a professionalized teacher education for vocational teachers are designed. Thereby, a discipline-related differentiation is placed in the center and teachers are understood as professionals who hold an academic degree. A fully trained teacher has earned a master’s degree.“ (author’s abstract; BIBB-Doku)

„Georg Spöttl nimmt das berufliche Bildungspersonal aus der international-vergleichenden Perspektive in den Blick. Die tatsächlichen Ausbildungsstandards für das berufliche Bildungspersonal sind international betrachtet sehr unterschiedlich. Auch innerhalb einzelner Länder gibt es sehr verschiedene Standards zwischen den verschiedenen Gruppen des beruflichen Bildungspersonals (z.B. Lehrkräfte oder betriebliches Ausbildungspersonal). Spöttl plädiert für die Weiterentwicklung von akademischen Ausbildungsstandards für das berufliche Bildungspersonal. Er untermauert sein Plädoyer mit der Darstellung der fachlichen und didaktischen Anforderungen an praktizierendes berufliches Bildungspersonal sowie mit den Positionen zentraler internationaler Organisationen zu diesem Thema. Darüber hinaus wird auf die Entwicklungen zur Professionalisierung des beruflichen Bildungspersonals in der ASEAN-Region näher eingegangen.“ (Hrsg.; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; P 3.2.1 Ausbilder; I 2.3.4 Asien; 370; Berufsschullehrer; Ausbilder; Berufsprofil; Lehrerbildung; Lehrerausbildung; Professionalisierung; Ausbildungsqualität; Internationaler Vergleich; Vietnam; Kambodscha